Alzheimer's Disease risk gene SORL1 affects synaptic function in hiPSC‐derived cortical neurons. (20th December 2022) - Williams, Charles A; Knupp, Allison; Mishra, Swati; Young, Jessica E.
Abstract: Background: The cellular endo‐lysosomal network (ELN) is implicated in Alzheimer's Disease pathology and Sortilin‐related receptor 1 ( SORL1 ) is important for normal function of the neuronal ELN. Loss of SORL1 in human induced pluripotent stem cell (hiPSC) derived neurons replicates early AD cytopathology, such as enlarged early endosomes. Work in our laboratory has shown that SORL1 deficiency results in decreased cell‐surface expression of glutamate receptor subunit GLUR1 and neurotrophic receptor TRKB. RNAseq of SORL1 deficient neurons revealed alterations in synaptic‐associated gene ontology transcripts. Together, these data implicate a potential functional consequence for SORL1 deletion. Here we investigate the impact of SORL1 on hiPSC‐derived neuronal synaptic function. Method: Neuronal cultures were differentiated using dual SMAD inhibition of previously generated wild‐type and SORL1 deficient hiPSCs. Following differentiation, neuronal cultures were either purified using cell surface markers CD44, CD184, and CD271 or passaged as mixed cultures for immunocytochemical (ICC) or electrophysiological experiments, respectively. For ICC, neurons were then fixed with paraformaldehyde and stained with experiment‐appropriate antibodies before imaging on a confocal scanning microscope. Mixed cultures were plated onto Axion Biosystems multiple electrode array (MEA) culture plates for electrophysiological analysis. MEA cultures were recorded twice a week for up to ten weeks post‐plating. Recordings and analysis were performed using Axion Biosystems Maestro Pro system. Result: Using ICC, we find alterations in alterations in synaptic protein and glutamate receptor co‐localization in SORL1 deficient neuronal cultures. When cultured on MEA plates, wild‐type and SORL1 deficient neuronal cultures are active and robust. Neuronal cultures develop glutamate signaling dependent patterns of activity, or network bursting. Neural firing rates are increased in SORL1 deficient neurons. Network bursting properties in SORL1 deficient are altered in comparison to wild‐type cultures, consistent with increased neural excitability. Conclusion: Loss of SORL1 alters hiPSC‐derived neuronal activity and synapse‐dependent activity. Further investigation is warranted into the alterations in neuronal physiology and will help us understand the role AD‐related ELN disruption plays in synaptic pathologies.